Analisis Perlakuan Akuntansi Atas Biaya Pengolahan Limbah Pabrik Kelapa Sawit (PKS) Ajamu Panai Hulu Berdasarkan Perspektif Syariah - Maysaroh Maysaroh; Kusmilawaty Kusmilawaty (ITB AAS INDONESIA Surakarta, 2023)
The study aims to determine and analyze the accounting treatment for the cost of processing waste from the Ajamu Palm Oil Mill (PKS), Panai Hulu. The accounting treatment includes identification, recognition, measurement, disclosure and presentation. This research is a qualitative research based on a descriptive approach using two types of data, namely primary data and secondary data. Primary data is obtained through the process of interviews, observation and documentation related to the research objectives, While secondary data is data obtained by researchers from other parties’ records in the form of company history and data related to research. The results of the research show that PT. Nusantara IV Ajamu Plantation has implemented an accounting treatment with processing costs. The results of the analysis stated that PT. Nusantara IV Ajamu Plantation has identified all costs related to the processing of palm oil mill effluent and recognized processing costs included in the general and administrative costs component as consideration that these environmental costs are related to company administration and general operations. In the process of measuring the cost of treating waste, it is stated at the cost incurred (Historical Cost). Disclosure regarding environmental issues in the waste treatment process is stated in the financial statements and is in accordance with the applicable accounting standards. Several similar costs are also presented in the company's income statement.